The Crisis of Intolerance and Primordialism in the Name Of Religion in Indonesia : a Case Study Of Pilkada DKI Jakarta at 2017 - Mahyuddin, Mahyuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2019)
The dynamic of politics in Jakarta was a politics incident that got attention from public (Ahok Case). Public sphere were not only loaded by physical violences but also various violences on the language level. This study aimed to grasp the phenomenon of political society behavior, particularly in social media by employing phenomenology-hermeneutics. The research interpreted variety of political behavior based on both intolerance and primordialism in action or representation of politic among supporters of The Governor of DKI Jakarta candidates. This study revealed that the representation of society behavior in public sphere and social media has been filled by violence intersecting with religion. These indications represented a social reality where violence in sign level (speech, writing, visual) had been covered by negative connotation. In this general election, public sphere were full of intolerance and primordialism so that political interaction and communication was filled by social friction and political conflict on those who had different choice and view.